Comparative efficacy of biological control agents for the management of cumin wilt caused by Fusarium oxysporum f.sp. cumini - S Sriram, B Ramanujam, Y K Sharma, S K Lodha, (Journal of Spices and Aromatic Crops, 2015)
Field experiments were conducted during rabi 2008-09 and 2009-10 for the management of cumin wilt caused by Fusarium oxysporum f.sp. cumini. The results showed that seed treatment with Trichoderma viride (10 g kg-1 of seed) and soil application (2.5 kg ha-1) recorded minimum percent disease incidence (PDI) of 18.5 (disease reduction of 51.8%) versus 38.4 in the control. It was on par with seed treatment and soil application with Aspergillus versicolor at 10 g kg-1 of seed and 2.5 kg ha-1, respectively which reduced the disease incidence by 45.4%. The chemical treatment i.e. seed treatment with carbendazim at 2.5 g kg-1 seed recorded PDI of 23.9 with 37.7% disease reduction. Among different treatments seed treatment and soil application with A. versicolor gave a seed yield of 246 kg ha-1 followed by P. fluorescens (222.6 kg ha-1). Treatment T. viride, recorded the highest yield of 258.2 kg ha-1. Hence, seed treatment at 10 g kg-1 and soil application at 2.5 kg ha-1 of T. viride was the most effective, eco-friendly disease management.